αSynuclein and Mitochondrial Dysfunction: A Pathogenic Partnership in Parkinson’s Disease? - David Protter; Charmaine Lang; Antony A. Cooper (Parkinson's Disease)
Parkinson’s Disease (PD) is a complex, chronic, progressive, and debilitating neurodegenerative disorder. Neither a cure nor effective long-term therapy exist and the lack of knowledge of the molecular mechanisms responsible for PD development is a major impediment to therapeutic advances. The protein αSynuclein is a central component in PD pathogenesis yet its cellular targets and mechanism of toxicity remains unknown. Mitochondrial dysfunction is also a common theme in PD patients and this review explores the strong possibility that αSynuclein and mitochondrial dysfunction have an inter-relationship responsible for underlying the disease pathology. Amplifying cycles of mitochondrial dysfunction and αSynuclein toxicity can be envisaged, with either being the disease-initiating factor yet acting together during disease progression. Multiple potential mechanisms exist in which mitochondrial dysfunction and αSynuclein could interact to exacerbate their neurodegenerative properties. Candidates discussed within this review include autophagy, mitophagy, mitochondrial dynamics/fusion/fission, oxidative stress and reactive oxygen species, endoplasmic reticulum stress, calcium, nitrosative stress and αSynuclein Oligomerization.